Strategies to Enhance Customer Loyalty at UD Bajuber Print Gresik - Romadhon, Harits; Surianto, Moh Agung (Jurnal Economic Resource, 2024)
Bajuber Print is a printing company that prioritizes customer satisfaction in a highly competitive printing industry. This study aims to identify various factors influencing customer loyalty using a qualitative approach, including in-depth interviews, focus group discussions, and direct observation. The data analysis revealed that consistent service quality, value-aligned pricing, positive customer experiences, and attractive loyalty programs are key factors in building and maintaining customer loyalty. These findings provide valuable strategic insights for Bajuber Print to formulate effective measures to enhance customer loyalty while strengthening the company's position in a competitive market.